Effect of moringa (Moringa oleifera) leaf supplementation on growth performance and feed utilization of Bocourti’s catfish (Pangasius bocourti) - Puycha, Kittisak; Yuangsoi, Bundit; Charoenwattanasak, Siripavee; Wongmaneeprateep, Sutee; Niamphithak, Pornthep; Wiriyapattanasub, Pattama (Agriculture and Natural Resources, 2017)
The optimal level of dietary moringa leaf was determined on the growth performance, feed utilization, digestibility and serum biochemistry of Bocourti’s catfish with mean wet weights of 3.72 ± 0.06 g per fish. Fish were fed with diets containing isonitrogenouse (350 g/kg crude protein) and isoenergetic (3000 kcal/kg) supplemented with dietary moringa leaf at 0 g/kg fish, 100 g/kg fish, 150 g/kg fish and 200 g/kg fish for 60 d. Fish were hand fed to apparent satiation twice a day. At the end of the experiment, a significant (p < 0.05) reduction in the growth performance was found as the moringa leaf inclusion increased in the diets, along with slightly poorer growth performance and feed utilization. Fish fed the diet containing moringa leaf at 100 g/kg demonstrated better growth than at the other inclusion levels, but it was not significantly different from the control group. The digestibility coefficient and protein digestibility were lower in fish fed with a higher inclusion of moringa leaf in the diets (p < 0.05). Pepsin digestibility and serum biochemical parameters were not different among all treatments (p > 0.05). The study indicated that dietary moringa leaf could be included in the Bocourti’s catfish diet at possibly not over 100 g/kg fish without a negative effect on the growth, feed utilization, digestibility and serum biochemistry.